2009
DOI: 10.1080/00016480802495446
|View full text |Cite
|
Sign up to set email alerts
|

Postural control and sensory perception in patients with Parkinson's disease

Abstract: LOS showed significant decrease in PD patients as compared with the control group (p<0.001, Kruskal-Wallis and Wilcoxon ranked test). The COP values increased significantly (p<0.001, Wilcoxon signed rank test) after sudden changes in the visual flow velocity in relation to the control group. After the visual stop the PD patient showed a spatial 'roaming' approaching the limits of stability and therefore impairing the postural control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
3
10
0
1
Order By: Relevance
“…This is in keeping with previous studies which reported that patients with PD could use other sensory modalities to maintain postural control during quiet standing in the absence of visual input [5,25,29]. On the other hand, with motion of visual scenes, patients with PD presented a greater reduction in BFR reduction than healthy subjects, suggesting that they had greater difficulty adapting to the dynamic visual field using other sensory inputs to maintain postural control [31].…”
Section: Page 13 Of 27supporting
confidence: 91%
See 1 more Smart Citation
“…This is in keeping with previous studies which reported that patients with PD could use other sensory modalities to maintain postural control during quiet standing in the absence of visual input [5,25,29]. On the other hand, with motion of visual scenes, patients with PD presented a greater reduction in BFR reduction than healthy subjects, suggesting that they had greater difficulty adapting to the dynamic visual field using other sensory inputs to maintain postural control [31].…”
Section: Page 13 Of 27supporting
confidence: 91%
“…In addition to abnormalities in the selection of compensatory sensory modalities and greater dependency on visual inputs during certain conditions [31,32], . This is in keeping with a previous study that assessed the postural control of patients with PD (HY Stages 2 to 4) and healthy subjects using the Sensory Organization Test [9].…”
Section: Page 14 Of 27mentioning
confidence: 99%
“…Parkinson’s disease (PD) is a common neurodegenerative disorder that affects balance and people with PD fall more often than age-matched healthy controls [1,2]. Fear of falling (FOF) is commonly experienced [3,4] and is a predictor of recurrent falls [5], a barrier to physical exercise [6], and is negatively associated with health-related quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fall rates are higher in studies that also include "near falls" 1 . Recent studies have shown that sensory input and sensory motor processing appear to be relevant in clinical issues in PD, such as instability in open spaces, postural control disorientation, or FOG [2][3][4][5][6][7][8] . One of the interesting points about the relationship between the changes in the cues of sensory information and postural control is the possibility to assess postural responses with these changes in order to understand all of the mechanisms involved in balance disorders in patients with PD.…”
Section: Introductionmentioning
confidence: 99%